2020
DOI: 10.1371/journal.pone.0229203
|View full text |Cite
|
Sign up to set email alerts
|

Implying social interaction and its influence on gaze behavior to the eyes

Abstract: Researchers have increasingly focused on how the potential for social interaction modulates basic processes of visual attention and gaze behavior. In this study, we investigated why people may experience social interaction and what factors contributed to their subjective experience. We furthermore investigated whether implying social interaction modulated gaze behavior to people's faces, specifically the eyes. To imply the potential for interaction, participants received either one of two instructions: 1) they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 74 publications
(132 reference statements)
2
13
0
Order By: Relevance
“…Participants' gaze was mainly directed to the face and within the face, especially to the eyes of their interaction partners. This pattern is consistent with findings of face exploration on static stimuli 47 , and in more naturalistic social encounters 4 , 48 , 49 . The investigation using dynamic stimuli has shown, amongst other things, that the fixation of the eye region is modulated by gaze behavior of the stimulus 20 and the facial expression displayed 50 .…”
Section: Study 3: Data Quality and Gaze Behavior In A Face-to-face Cosupporting
confidence: 89%
“…Participants' gaze was mainly directed to the face and within the face, especially to the eyes of their interaction partners. This pattern is consistent with findings of face exploration on static stimuli 47 , and in more naturalistic social encounters 4 , 48 , 49 . The investigation using dynamic stimuli has shown, amongst other things, that the fixation of the eye region is modulated by gaze behavior of the stimulus 20 and the facial expression displayed 50 .…”
Section: Study 3: Data Quality and Gaze Behavior In A Face-to-face Cosupporting
confidence: 89%
“…To investigate participants' looking behavior when in the presence of another person, Laidlaw, Foulsham, Kuhn, and Kingstone (2011) placed participants in a waiting room with a live confederate or with a videotaped confederate displayed on a screen. They showed that participants are keen to look at a videotaped confederate in a waiting room but not at a live confederate (for recent work on this topic, see Holleman, Hessels, Kemner, & Hooge, 2020). The phenomenon of not looking at other people out of courtesy has been well described by Goffman (1966).…”
Section: Looking Behavior To Humans and Human Facesmentioning
confidence: 98%
“…One important function of gaze behavior is to acquire visual information from the world, however, within a social context, gaze may also signal important information to others which may be used to initiate and facilitate social interaction (see e.g., Gobel et al, 2015;Risko et al, 2016). In a series of experiments, researchers have systematically varied whether, and the degree to which social interaction between two people was possible, and measured how gaze was modulated as a function of the social context (Laidlaw et al, 2011;Gobel et al, 2015;Gregory and Antolin, 2019;Holleman et al, 2020). In other studies, researchers have been explicit about the taskdemands and social contexts that elicit specific patterns of gaze behavior, for example, in the context of face-to-face interactions and conversational exchanges (Ho et al, 2015;Hessels et al, 2019).…”
Section: The Field Of Social Attention: Away From the Real-world And mentioning
confidence: 99%